Japan’s Balanced Strategy to Face China’s Threat in South China Sea Dispute - Darmawan, Arief Bakhtiar (JURNAL ILMU SOSIAL, 2020)
This paper aims to analyze Japan’s foreign policy related to the dispute in the South China Sea (SCS). Even though Japan has no sovereignty claims, it has considerable interests in the SCS region. Japan, which is poor in natural resources, depends on energy imports, most of which are shipped through SCS. As an advanced industrial state, Japan must continue to meet domestic energy demand. However, the SCS area has a potential conflict due to Chinese assertive behavior as the main factor that could threaten Japanese interests. The author use qualitative method with relevant literature studies and official government documentation to conduct a descriptive analysis of the research findings. The results of the study indicate that Japan is implementing a balanced strategy to deal with the potential threat of China. Balancing against threats is conducted in internal ways, e.g. internal reinforcement, and external ways, e.g. forming and strengthening cooperation with other countries outside the United States (US). Since Japan's limitations in military aspect hindered their internal reinforcement, this study emphasizes Japan's external balance strategy. The increasingly dubious US commitment in the Asia Pacific has made Japan strengthen defense cooperation with Southeast Asian countries such as Indonesia, the Philippines and Vietnam. The three countries have interest in SCS and provide access that conforms to Japanese interests.